An Integrative Analysis of Foot‐and‐Mouth Disease Virus Carriers in Vietnam Achieved Through Targeted Surveillance and Molecular Epidemiology. Issue 2 (24th August 2015) - de Carvalho Ferreira, H. C.; Pauszek, S. J.; Ludi, A.; Huston, C. L.; Pacheco, J. M.; Le, V. T.; Nguyen, P. T.; Bui, H. H.; Nguyen, T. D.; Nguyen, T.; Nguyen, T. T.; Ngo, L. T.; et al.
Summary: Foot‐and‐mouth disease (FMD) is a major constraint to transboundary trade in animal products, yet much of its natural ecology and epidemiology in endemic regions is still poorly understood. To address this gap, a multidisciplinary, molecular and conventional epidemiological approach was applied to an investigation of endemic FMD in Vietnam. Within the study space, it was found that 22.3% of sampled ruminants had previously been infected with FMD virus (FMDV), of which 10.8% were persistent, asymptomatic carriers (2.4% of the total population). Descriptive data collected from targeted surveillance and a farm questionnaire showed a significantly lower prevalence of FMDV infection for dairy farms. In contrast, farms of intermediate size and/or history of infection in 2010 were at increased risk of FMD exposure. At the individual animal level, buffalo had the highest exposure risk (over cattle), and there was spatial heterogeneity in exposure risk at the commune level. Conversely, carrier prevalence was higher for beef cattle, suggesting lower susceptibility of buffalo to persistent FMDV infection. To characterize virus strains currently circulating in Vietnam, partial FMDV genomic (VP1) sequences from carrier animals collected between 2012 and 2013 ( N = 27) and from FMDV outbreaks between 2009 and 2013 ( N = 79) were compared by phylogenetic analysis. Sequence analysis suggested that within the study period, there were two apparent novel introductions of serotype A viruses and that the dominant lineage of serotype O in Vietnam shifted from SEA/Mya‐98 to ME‐SA/PanAsia. FMDV strains shared close ancestors with FMDV from other South‐East Asian countries indicating substantial transboundary movement of the predominant circulating strains. Close genetic relationships were observed between carrier and outbreak viruses, which may suggest that asymptomatic carriers of FMDV contribute to regional disease persistence. Multiple viral sequences obtained from carrier cattle over a 1‐year period had considerable within‐animal genetic variation, indicating within‐host virus evolution.